Development of a Smart Village Application to Support Local Administration and Public Service Delivery in Vaviquinea Village, Maubara Municipality - Jaime Da C.L. Soares; Apolinario dos Santos; Armindo da Costa; Cristiano C. Abel; Constantino F.S. Amaral (International Journal Labs, 2026)
Digital transformation in rural governance is crucial for improving administrative efficiency and the quality of public services, particularly in areas with limited infrastructure. Currently, most administrative processes at the Desa level are still conducted manually, resulting in data fragmentation, prolonged service times, and limited access to information. This study aims to design, develop, and implement a web-based Smart Village application in Desa Vaviquinea, Maubara Administrative Post, Timor-Leste. A Research and Development (R&D) approach was employed using the System Development Life Cycle (SDLC) framework, which includes requirements analysis, system design, implementation, functional testing, and user evaluation. Data were collected through field observations, semi-structured interviews, document analysis, and user questionnaires (N = 50; 10 Desa staff and 40 community members). The application integrates population data management, administrative letter services, dissemination of public information, as well as online application submissions and complaint handling. Evaluation results indicate a 60% reduction in processing time, a 2% error rate, and a user satisfaction score of 4.2 out of 5, demonstrating improvements in administrative efficiency, transparency, and responsiveness. This study presents a contextual Smart Village model for rural areas in Timor-Leste and can be replicated in other Desas with similar characteristics .